Integrasi Ekosistem Karbon Biru dalam Kebijakan Penangkapan Ikan Terukur (PIT) di Indonesia - Sri Rizkhy Saleh; Atika Puspita Marzaman (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
Blue carbon ecosystems play a strategic role in mitigating climate change through their ability to absorb and store carbon significantly. However, uncontrolled exploitation of marine resources, such as overfishing, destructive fishing methods, and fishing gear waste, have threatened the sustainability of blue carbon ecosystem. Penangkapan Ikan Terukur (PIT) policies implemented by the Indonesian government aims to realize sustainable fisheries by regulating fishing quotas based on zoning. This reserach aims to identify the urgency of integrating blue carbon ecosystems into PIT policies in Indonesia to maintain the sustainability of marine resources and support climate change mitigation. Using qualitative descriptive methods based on literature studies, this research found that integrating blue carbon ecosystems into PIT policies can provide significant ecological benefits. Strict monitoring, restoration of blue carbon ecosystem habitats, and implementation of scientific data-based policies are needed to ensure the success of this policy. This integration is expected to be able to maintain marine ecosystems, support sustainable fisheries, and contribute to global climate change mitigation targets.